Current transport mechanisms in metal – high-k dielectric – silicon structures - Gomeniuk, Y.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
The mechanism of current transport in several high k -dielectric, including
rare earth metal oxides (Gd₂O₃, Nd₂O₃), ternary compounds (LaLuO₃) and rare earth
metal silicate (LaSiOx) thin films on silicon was studied using current-voltage ( I - V )
and conductance-frequency measurements at temperatures 100-300 K. It was
shown that the current through the dielectric layer is controlled either by Pool-Frenkel
mechanism of trap-assisted tunneling or by Mott’s variable range hopping conductance
through the localized states near the Fermi level. From the results of measurements, the
dynamic dielectric constant k of the material, energy positions and bulk concentrations of
traps inside the dielectric layers were determined.